Charge storage kinetics of MoS2 flower decorated reduced graphene oxide for quasi solid-state symmetric supercapacitor. (February 2023) - Jhankal, Deependra; Khan, Mohammad Saquib; Jhankal, K.K.; Sachdev, K.
Abstract: In this study, micro flower-like molybdenum disulfide (MoS2 ) is directly grown on reduced graphene oxide (rGO) sheets by a new one-pot facile hydrothermal strategy with different MoS2 -rGO combinations (such as 1:1, 1:2 and 2:1, respectively). The structural and morphological study demonstrate that MoS2 flowers are uniformly distributed on the rGO sheets. The capacitive performance of synthesized samples has been evaluated by various electrochemical techniques, using a three-electrode set-up in 1 M Na2 SO4 electrolyte. The electrochemical results reveal that the MoS2 -rGO (1:2) offers the highest capacitance of 352 F g −1 at a current density of 0.2 A g −1 . Further, the charge storage kinetics of MoS2 -rGO (1:2) electrode have been evaluated by in-depth analysis of the Cyclic Voltammetry (CV) profile, implying that the charge storage mechanism contributes to both capacitive and diffusion-controlled processes. Three symmetric supercapacitor (SC) devices are fabricated using three aforementioned compositions as the active material with polyvinyl alcohol (PVA)/Na2 SO4 hydrogel membrane as the separator-less electrolyte. The symmetric SC device (MoS2 -rGO (1:2) || MoS2 -rGO (1:2)) based on MoS2 -rGO (1:2) as the electrode material demonstrates maximum capacitance value 256 F g −1 at 0.15 A g −1 . This strategy to combine the appropriate amount of MoS2 with rGO sheets has enhanced the electrochemical performance of MoS2 -rGO composite due to the formation of a hetero-interface between MoS2 and rGO composite leading to fast ion propagation and facilitate the development of advanced quasi-solid-state energy storage devices. Graphical abstract: Image 1 Highlights: The MoS2 flower decorated on rGO utilized as advanced electrode material for supercapacitor electrode. The MoS2 -rGO (1:2) possesses the maximum value of specific capacitance (254 Fg -1 ). Kinetics study shows the both diffusive and capacitive controlled charge storage mechanisms in MoS2 -rGO (1:2) electrode. Synergistic effect of inter-connected nanocomposite structure improves the sodium ion storage.